Moodling through: the virtual world of the palliative medicine trainee. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Marley, Kate; Gaunt, Kathryn; Groves, Karen; Coackley, Alison
Abstract : Background: Trainees in Palliative Medicine in the Mersey Deanery require experience of a variety of work settings during training which leads to them being scattered within the region. Some services have only one trainee and there are few opportunities for the trainees to meet. Regular contact between trainee colleagues provides the benefit of peer support in an emotionally challenging specialty. Informal discussions and exchange of clinical and educational information can be maintained and there are opportunities to discuss new developments within the specialty with colleagues at a similar level to oneself. In the current economic climate UK health chiefs are striving to reduce cost in all areas of healthcare including study budgets and trainees must be creative in their efforts to fulfil their curriculum requirements. Addressing the problems: To enhance the educational and supportive contact between trainees, an online electronic learning platform has been developed specifically for Mersey Deanery Palliative Medicine trainees. The platform used is Moodle, a free and open-source virtual learning environment. Trainees have a personal login and password and are then able to access: Links to resources and websites covering the Palliative Medicine curriculum and e-portfolio A monthly journal club Fora for discussion of challenging anonymised clinical cases and provision of peer support. A revision area for trainees sitting the specialty examination Calendar marking important dates for trainees Progress Report: The website is used regularly. Trainees have more contact with each other than previously and trainees in different locations are participating in online clinical discussions. There are over 200 trainee activity logs per month across the site and there have been over 2800 activity logs since the site was set up in March 2011. Formal evaluation will take place at the end of the first year of the site's use.